Health Technology Assessment and Biomedical Engineering: Global trends, gaps and opportunities. (October 2019) - Pecchia, L.; Pallikarakis, N.; Magjarevic, R.; Iadanza, E.
Highlights: Health Technology Assessment (HTA) is core topic for biomedical engineering. There is a real need for more biomedical engineers (BME) trained in HTA. High quality HTA training material designed for BME is freely available. BME as a profession is getting recognition in Europe and from United Nations agencies. WHO counted 1 million of biomedical engineers and technicians worldwide. Abstract: The diffusion of medical devices is expanding at an astonishing rate. The increasing number of novel patents per year suggests this growth will continue. In contrast to drugs, medical devices are intrinsically dependent on the environment in which they are used and how they are maintained. This created an unprecedented global need for well-trained biomedical engineers who can help healthcare systems to assess them. The International Federation for Medical and Biological Engineering (IFMBE) is the global scientific society of biomedical engineers in official relations with the United Nations World Health Organisation (WHO) and has been very active in promoting the role of the biomedical engineer in Health Technology Assessment (HTA). The IFMBE Health Technology Assessment Division (HTAD) is the IFMBE operative branch in this field, promoting studies, projects and activities to foster the growth of this specific and very important science sector, including summer schools, training material, an HTA eLearning platform, HTA guidelines, awards and more. This article describes the vision, the mission and the strategy of the HTAD, with a focus on the results achieved and the impact this is having on global policymaking.